Анализ клонового разнообразия двух видов апомиктических дождевых червей (Lumbricidae: Aporrectodea) и проблема изменчивости мелких и крупных организмов - Межжерин, С.В.; Власенко, Р.П.; Гарбар, А.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The comparative analysis of clone diversity of two triploid apomictic earthworms species of Aporrectodea genus is done in 44 samples from the territory of Ukraine. As a result, not only amphimictic A. caliginosa and A. longa, but also apomictic A. trapezoides (174 ind.) and A. rosea (235 ind.) represented with 17 and 96 clones respectively are found. Clone diversity indices calculated according to the Shannon — Weaver index differed in two latter species in the average sampling by 4 and in the overall sampling by 1.8 times. The results corroborate the tendency characteristic of apomictic earthworms: small species have higher level of genetic diversity than big ones. So, the tendency typical of all animals is confirmed: under same conditions, small organisms have higher level of genetic diversity in comparison with big ones. This universal tendency is explained by a higher speed of metabolic and physiological processes characteristic of quickly maturing small animals.